DEVELOPING FLIPBOOK ON AROMATHERAPY CANDLE MAKING FROM USED COOKING OIL TO STRENGTHEN PANCASILA STUDENT PROFILE IN HYDROCARBON LESSON - Astuti, Tiwi Nur; Syaadah, Rika Siti; Islami, Oktavianti Nur (Science Education, Institut Agama Islam Negeri Ponorogo, 2025)
This research aims to develop a flipbook on making aromatherapy candles from used cooking oil, integrated with the Project to Strengthen the Pancasila Student Profile (P5). The flipbook is designed not only to enhance students' conceptual understanding of hydrocarbon materials but also to instill essential P5 values. The development of aromatherapy candle flipbooks from used cooking oil integrates the value of sustainable lifestyles in the P5 by encouraging learners to manage household waste creatively and environmentally friendly as part of contextual learning. The study employed a Research and Development (RnD) approach using ADDIE model, which includes five stages: Analyze, Design, Develop, Implement, and Evaluate. The development process focused on aligning learning content with students' needs and incorporating multimedia features to support independent and engaging learning. A total of 35 students in grade XI of MAN 3 Jakarta were selected for the limited trial of the flipbook implementation. The results of the validation and implementation phases demonstrated that the flipbook is highly effective, receiving an overall interpretation score of 88%, consists of 89% for visual design quality, 87% for content relevance, and 88% for ease of media access which are all in the excellent category. The flipbook not only presents hydrocarbon concepts and step-by-step instructions for candle making but also integrates P5 values, environmental awareness through waste management solutions, fun facts, reflection activities, and interactive multimedia. Based on these findings, the developed flipbook highly effective to be a suitable and innovative digital teaching material that can enhance student engagement, improve understanding, and serve as a model for integrating character education into science learning.